Use of ontology approach to standardized scientific experimental data representation - Azram, Nur Adila; Atan, Rodziah; Kasim, Shahreen (Zibeline Internasional Publishers, 2018)
Scientific experimental data are rapidly produced by researchers in various research domains. It is difficult to manage and organize different experimental data because of different data sources involved. There is a need to have a standard scientific experimental data representation so that data from different sources can be represented in a standard format. One effective way to standardize scientific experimental data representation is through ontology approach. Ontology can provides a controlled vocabulary of terms that will give a standard name to the parameters of scientific experimental data. In this paper, we focused on standardizing scientific experimental data from laboratory instruments. We explained the flows of the ontology schema design and shows some of the parameters in the proposed ontology schema for instruments experimental data.